Pilot Study: Malaysian University Students’ Attitudes towards Wiki Writing as an Alternative Assessment - Hussein, Nur Hafezah (Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
Recently, alternative assessment has gained increasing attention especially in the context of Malaysian tertiary education. In line with this, the present study aimed at investigating Malaysian university students’ attitudes towards the use of wiki writing as an alternative assessment in English learning. 29 university students participated in this study and data was collected via a questionnaire. Descriptive statistics were employed in analysing the data. Results showed that the students’ attitudes were negative towards the use of wiki writing as an alternative assessment for their English writing. They believed that alternative assessment is time-consuming and ignores students’ writing skills. The students further expressed their preference for traditional written tests over alternative assessment. Limitations of the study as well as recommendations were further discussed.